2016
DOI: 10.1002/ptr.5665
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cocoa Flavanols on Cardiovascular Health

Abstract: The aim of the study was to review the effect of cocoa flavanols on cardiovascular health, with emphasis on the doses ingested, and to analyze a range of cocoa products for content of these compounds. PubMed was searched from 2010 to locate systematic reviews (SR) on clinical effects of chocolate consumption. Thirteen SRs were identified and reviewed, and provided strong evidence that dark chocolate did not reduce blood pressure. The evidence was however strong for an association with increased flow-mediated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 113 publications
(149 reference statements)
2
30
0
2
Order By: Relevance
“…Previously, we have shown that pooling of exploratory studies (Ried et al, 2012) may overestimate the effect size on blood pressure (Vlachojannis, Erne, Zimmermann, & Chrubasik-Hausmann, 2016). This is one reason why we did not pool the data and emphasize as others (Borghi & Cicero, 2017;Cicero et al, 2017) that rigorous studies with a confirmatory design should provide data on the magnitude of blood pressure, blood lipids, and atherosclerosis decrease.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we have shown that pooling of exploratory studies (Ried et al, 2012) may overestimate the effect size on blood pressure (Vlachojannis, Erne, Zimmermann, & Chrubasik-Hausmann, 2016). This is one reason why we did not pool the data and emphasize as others (Borghi & Cicero, 2017;Cicero et al, 2017) that rigorous studies with a confirmatory design should provide data on the magnitude of blood pressure, blood lipids, and atherosclerosis decrease.…”
Section: Discussionmentioning
confidence: 97%
“…; Vlachojannis et al . ). In many studies, regular consumption of cocoa, or a flavanol extract of cocoa, reduced blood pressure, blood cholesterol, F2‐isoprostanes and susceptibility of LDL to oxidation.…”
Section: Human Intervention Studies On Flavanols and Flavanol‐rich Fomentioning
confidence: 97%
“…(2) We consider that their conclusion-"At present there is no evidence that the doses of cocoa flavanols and epicatechins used in the studies included reliably decrease blood pressure" (Vlachojannis et al, 2016) -is not a reasonable interpretation of the literature. The authors point out the variability of responses in individual studies and note that repeat seated clinic measures of BP are inherently variable and therefore an unreliable means to detect change.…”
Section: Dear Editormentioning
confidence: 98%
“…
Keywords: chocolate; flow mediated dilatation; blood pressure.
Dear editor,We read with interest the recent article by Vlachojannis and colleagues in which they summarised reviews of the effects of cocoa derived flavanols on cardiovascular function (Vlachojannis et al, 2016). We agree that there is a lack of consistency in findings, particularly in relation to blood pressure (BP), and that better reporting of flavanol content in research reports and on consumer products is needed.
…”
mentioning
confidence: 99%